Russia Monthly Economic Developments, August 2015 - Hansl, Birgit; Baffes, John; Emelyanova, Olga; Matytsin, Mikhail; Ulatov, Sergei; Vashakmadze, Ekaterine (World Bank, Washington, DC, 2015)
Russia’s economy contracted 4.6 percent in the second quarter, year-on-year, after a 2.2 percent contraction in the first quarter, but in June the pace of contraction slowed. Russia’s second quarter balance of payment remained stable despite a weaker trade balance as the current account improved and capital outflows moderated. Receding oil prices and a further cut in the key policy rates in July brought the ruble exchange rate down to its lowest level since February. Preliminary poverty statistics for the first quarter of 2015 show a significant increase in the number of poor people.